Amine assisted top-down delamination of the two-dimensional metal–organic framework Cu2(bdc)2. Issue 47 (17th November 2017) - Kutzscher, Christel; Gelbert, André; Ehrling, Sebastian; Schenk, Claudia; Senkovska, Irena; Kaskel, Stefan
Abstract : Two different strategies of amine assisted delamination of 2D MOFs were developed. Abstract : A chemically assisted top-down method for the synthesis of MOF-nanoplates was developed applying amine based delamination agents. Applied on a well described model structure, the layered MOF Cu2 (bdc)2 (DMF)2 (bdc – 1, 4-benzenedicarboxylate), two different strategies of amine assisted delamination turned out to be successful to obtain nanoplates. Particles with thicknesses of around 70 nm were obtained by direct delamination of crystals using octylamine. The surfactant (polyvinylpyrrolidone) assisted synthesis combined with a post-synthetic amine delamination step enabled a further reduction of the thickness of the MOF nanoplates down to 4–14 nm.